PENGARUH ENTERPRISE RESOURCH PLANNING (ERP) DAN KOMPETENSI SUMBER DAYA MANUSIA (SDM) TERHADAP KUALITAS PENYAJIAN LAPORAN KEUANGAN PADA PT. PLN (PERSERO) UIP3B SULAWESI - ISWANDY, ISWANDY; DIANA, FINA; IRMAWATI, IRMAWATI (Patria Artha Management Journal, 2024)
The purpose of this research is to determine the influence of Enterprise Resource Planning (Erp) and Human Resource Competency (HR) on the quality of financial report presentation at Pt. PLN (Persero) UIP3B Sulawesi.This type of research is quantitative research and is classified as population research using a questionnaire as a data collection tool with a population size of 51 strategic employees of the company PT PLN (Persero) Sulawesi Expense Management Center Distribution Unit (P3B) who use ERP.The research results show that Enterprise Resources Planning (ERP) has no and no significant effect on the quality of financial report presentation. Human Resource Competency has a positive and significant effect on the quality of financial report presentation. There is an influence of Enterprise Resources Planning (ERP) and Human Resources Competency which simultaneously influence the quality of financial report presentation.